Pemasaran Media Sosial Memoderasi Hubungan Antara Destination Image dan Tourist Satisfaction Terhadap Revisit Intention (Studi pada Wisatawan yang Pernah Berkunjung Ke Jimbaran) - Gede Mas Sahasra Kirana Bhuwana Mandala Wijaya; Ni Made Asti Aksari (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
Tourism is one of the sectors that continues to experience development, especially in the era of digitalization. One of an attractive tourist destinations in Bali, Indonesia is Jimbaran. This research was conducted on tourists who have visited Jimbaran. The purpose of this study is to explain how social media marketing moderates the relationship between destination image and tourist satisfaction on revisit intention. This study uses the theory of Planned Behavior with a sample size of 100 people and uses purposive sampling technique. Data collection in this study was carried out by questionnaire method via google form. The data analysis technique used in this research is Moderated Regression Analysis (MRA). The results showed that destination image and tourist satisfaction have a positive and significant effect on revisit intention, and social media marketing moderates the influence of destination image and tourist satisfaction toward revisit intention. The findings of this study can help Jimbaran Village authorities in developing policies aimed at increasing tourist visitation by utilizing social media to strengthen the influence of destination image and tourist satisfaction on tourists revisit intention to Jimbaran,